Natural Compounds: A Hopeful Promise as an Antibiofilm Agent Against Candida Species - Shariati, Aref; Didehdar, Mojtaba; Razavi, Shabnam; Heidary, Mohsen; Soroush, Fatemeh; Chegini, Zahra (Frontiers in Pharmacology, 2022)
The biofilm community of Candida is resistant to various antifungal treatments. The ability of Candida to form biofilm on abiotic and biotic surfaces is considered one of these fungi' most important virulence factors. Extracellular DNA and exopolysaccharides could lower the antifungal penetration to the deeper layers of the biofilm, which is a serious concern that is promoted by the emergence of azole-resistant isolates and selection of Candida with decreased antifungal susceptibility. Since the biofilms' resis¬tance to common antifungal drugs has become more widespread in recent years, more investigations should be performed to produce novel, inexpensive, non-toxic, and effective treatment approaches by mainly controlling the biofilm-associated infections. Accordingly, scientists have used various natural compounds for inhibiting and degrading Candida biofilm. Curcumin, cinnamaldehyde, eugenol, carvacrol, thymol, terpinen-4-ol, linalool, geraniol, cineole, saponin, camphor, borneol, camphene, carnosol, citronellol, coumarin, epigallocatechin gallate, eucalyptol, limonene, menthol, piperine, saponin, α-terpineol, β–pinene and citral are the major natural compounds that have been used widely for inhibition and destruction of Candida biofilm. These compounds not only suppress fungal adhesion and biofilm formation, but also destroy mature biofilm community of Candida. Additionally, natural compounds have interactions with various cellular pathways of Candida such as ABC drug transporter, cell cycle progression, and Mitochondrial activity, as well as ergosterol, chitin and glucan biosynthetic. Notably, the use of different drug-delivery platforms enhanced the antibiofilm efficacy of natural compounds. Therefore, drug-platforms should be considered as a potential candidate for coating catheter and other medical materials surface. Additionally, a future goal will be to develop natural compounds as antibiofilm agents that can be used for the treatment of multi-drug resistant Candida biofilm, since the exact interactions of natural compounds and these biofilm structures are not elucidated. Nevertheless, in vitro toxicology analysis and animal experiments are required to confirm the reported molecular antibiofilm effect of natural compounds against Candida biofilm. In the present review article, we have discussed various aspects of natural compounds usage for inhibition and destruction of Candida biofilm along with different methods and procedures that have been used for improving these compounds efficacy against Candida biofilm.